Mathematical model and experiment analysis of pressure fluctuation inside dual-stack drainage system in residential buildings. (12th May 2022) - Guan, Y.; Yan, X.; Fang, Z.; Ren, S.
Abstract: The final velocity was put forward to study the water flow characteristics inside the building drainage system; however, it is more suitable for low-rise and multi-storey buildings, not for high-rise buildings. This study revealed the drainage transient characteristics of a double stack drainage system in high-rise residential buildings. Based on the final velocity, the air-water interaction mechanism and two-phase flow conditions in high-rise residential drainage stacks were discussed. An influence model of drainage system flow rate on pressure fluctuation under the change of state parameters such as ventilation rate, pipe wall roughness and building height was established. The pressure limit and flow rate data were obtained through full-scale experiments. The pressure limit and flow rate model were simplified to . After the data were verified, the fitting coefficients A, B and C were linear to the floor height. HIGHLIGHTS: This study puts forward a model of drainage system flow rate on pressure fluctuation under the change of state parameters in double stack drainage system in high-rise residential buildings. The pressure limit and flow rate data were obtained through full-scale experiments in high-rise experiment tower. The fitting coefficient A, B and C of pressure fluctuation model were linear to the floor height. Graphical Abstract